ADAM17 is the main sheddase for the generation of human triggering receptor expressed in myeloid cells (hTREM2) ectodomain and cleaves TREM2 after Histidine 157. (1st November 2017) - Feuerbach, Dominik; Schindler, Patrick; Barske, Carmen; Joller, Stefanie; Beng-Louka, Edwige; Worringer, Katie A.; Kommineni, Sravya; Kaykas, Ajamete; Ho, Daniel J.; Ye, Chaoyang; Welzenbach, Karl; Elain, Gaelle; et al.
Highlights: ADAM17 is the main sheddase for cleavage of hTREM2 ectodomain. ADAM17 cleaves TREM2 between histidine 157 and serine 158. Cleavage does not change for human AD susceptibility mutation R47H. Abstract: Triggering receptor expressed in myeloid cells (TREM2) is a member of the immunoglobulin superfamily and is expressed in macrophages, dendritic cells, microglia, and osteoclasts. TREM2 plays a role in phagocytosis, regulates release of cytokine, contributes to microglia maintenance, and its ectodomain is shed from the cell surface. Here, the question was addressed at which position sheddases cleave TREM2 and what are the proteases involved in this process. Using both pharmacological and genetic approaches we report that the main protease contributing to the release of TREM2 ectodomain is ADAM17, (a disintegrin and metalloproteinase domain containing protein, also called TACE, TNFα converting enzyme) while ADAM10 plays a minor role. Complementary biochemical experiments reveal that cleavage occurs between histidine 157 and serine 158. Shedding is not altered for the R47H-mutated TREM2 protein that confers an increased risk for the development of Alzheimers disease. These findings reveal a link between shedding of TREM2 and its regulation during inflammatory conditions or chronic neurodegenerative disease like AD in which activity or expression of sheddases might be altered.